2015
DOI: 10.3389/fpsyg.2015.00165
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of character strengths with coping, work-related stress, and job satisfaction

Abstract: Personality traits have often been highlighted to relate to how people cope with stressful events. The present paper focuses on character strengths as positive personality traits and examines two basic assumptions that were derived from a core characteristic of character strengths (i.e., to determine how individuals deal with adversities): (1) character strengths correlate with coping and (2) buffer the effects of work-related stress on job satisfaction. Two different samples (i.e., a mixed sample representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 48 publications
4
89
0
9
Order By: Relevance
“…Individuals with high character strengths are likely to perceive less stress and demonstrate healthy psychophysiological responses (Duan et al, 2015; Harzer & Ruch, 2015; Li & Liu, 2016). HR, SBP, and DBP are believed to be highly physical stress tests in comparison with state anxiety, which is a mental stress test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with high character strengths are likely to perceive less stress and demonstrate healthy psychophysiological responses (Duan et al, 2015; Harzer & Ruch, 2015; Li & Liu, 2016). HR, SBP, and DBP are believed to be highly physical stress tests in comparison with state anxiety, which is a mental stress test.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, wisdom strength provides participants with coping strategies to present adaptive responses to stress. Another study identified intellectual, emotional, and interpersonal strengths as coping-related components in a work-stress area, and these strengths significantly mediate the negative effect of stress on job satisfaction (Harzer & Ruch, 2015). Papousek et al (2010) examined the influence of trait positive affect on cardiovascular stress responses and found that a high trait positive affect is associated with complete cardiovascular and subjective post-stress recovery.…”
Section: Discussionmentioning
confidence: 99%
“…They are components of the good character, morally valued, trait-like and can be facilitated by rituals or institutions (Peterson and Seligman, 2004). Furthermore, they are considered essential, as they relate to stress coping behavior in health care professionals (Harzer and Ruch, 2015). Character strengths have positive associations with overall perceived health (Proyer et al, 2014) and a unique value in predicting physical health (Hanks et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Martin () reported that personal strengths and positive work environment are critical to promote people's job motivation, job contribution and job satisfaction. Through motivating people's inherent talents, strengths and increasing interaction with a positive environment, positive psychotherapy could help participants overcome adversities and become more engaged in work and life (Harzer & Ruch, ; Pang & Rush, ).…”
Section: Discussionmentioning
confidence: 99%